STUDIES ON MENINGOCOCCUS INFECTION : VII. THE STUDY OF AN ISOLATED EPIDEMIC - Rake, Geoffrey (The Rockefeller University Press, 1935)
The investigation of this isolated epidemic of meningococcus meningitis at a C.C.C. camp gave an opportunity to examine the carrier state in contacts carrying what were presumably virulent epidemic strains of organisms. With the aid of Miller's technique for the enhancement of the demonstrable virulence of meningococci for mice, it proved possible to test the virulence of the carrier strains from Camp Rusk. These results were consistent despite the interval of from 3 to 4 weeks which intervened between the isolation of the strains and the virulence titrations. Type I strains were found to have a high virulence, while the virulence of Type II strains was moderately high but definitely less than that of the Type I, and atypical strains and strains of N. catarrhalis isolated from carriers showed a very low virulence. The question of the precise nature of the carrier state was investigated. No evidence has been obtained yet as to the existence of a relationship between pharyngitis, coryza or upper respiratory disease and the presence and degree of the carrier state. This is unlike the situation with regard to pneumococcus carriers. On the other hand, it has proved possible to demonstrate reactions within the body to the meningococci in the nasopharynx, consisting of the formation of agglutinins and protective antibodies in the blood serum. 32.3 per cent of Type I and 60 per cent of Type II carrier sera showed moderate or good agglutinins for homologous organisms and 80 per cent of Type I and 40 per cent of Type II sera showed moderate or good protective antibodies against virulent homologous strains. No idea could be obtained as to the relationship of the presence or absence and the degree of serological reaction and the duration of the carrier state.